The role of Hox proteins in leukemogenesis: insights into key regulatory events in hematopoiesis - Eklund, Elizabeth (Critical reviews in oncogenesis, 2011)
Acute myeloid leukemia (AML) is a heterogeneous disease with highly variable prognoses. Identification of recurring chromosomal translocations provides some prognostic information for individual AML subjects. Population based gene-expression profiling studies also identified abnormalities relevant to prognosis. Such studies associate increased expression of a set of homeodomain transcription factors with poor prognosis in AML. This set includes HoxB3, B4, A7-11 and Meis1, which are dysregulated as a group in the bone marrow in poor prognosis AML. Aberrant expression of these homeodomain transcription factors is found in AML with chromosomal translocations involving the MLL, MYST3 and CREBBP genes, and in a poor prognosis subset with normal cytogenetics. Studies in murine models suggest that Hox protein overexpression is functionally significant for myeloid malignancies. Overexpression of individual Hox proteins expanded various bone marrow populations in vitro, leading to myeloproliferation and in some cases differentiation block and AML in vivo. Therefore, dysregulated expression of key Hox target genes may contribute to adverse prognosis in AML. Identification of these genes will provide insights into the pathobiology of prognosis in AML. Studies are beginning to identify Hox target genes which may be rational targets for therapeutic approaches to this poor prognosis leukemia subset.